Analisis Tebal Perkerasan Jalan Provinsi Berdasarkan Manual Desain Perkerasan (MDP) 2017 - Nugraha, Aditya; Sulistyorini, Rahayu; Ofrial, Siti Anughrah Mulya Putri; Herianto, Dwi (Universitas Lampung, 2023)
Highways are one of the main infrastructures that are very important to sustain the activities of an area, so a well-designed pavement with precise thickness is needed to maintain the long-term safety and comfort of user during traffic. This study aims to determine the type and thickness of the road pavement structure used on provincial roads based on the 2017 Manual Pavement Design (MDP). The research was held on Jendral Sudirman street intersection Kalirejo district market to the end of the intersection of main market pringsewu on Makam KH. Ghalib street with a road length of 16,392 km. The planned lifespan using the 2017 Manual Pavement Design (MDP) is 20 years with a traffic growth rate factor of 3,5% and the Cumulative Equivalent Single Axle (CESA) value is 4.062.772,21. This research can be used as material for consideration in the construction and reconstruction of roads in Lampung province.